FORWARD ERROR CONTROL PADA JARINGAN WIRELESS ATM BERBASIS CDMA - HAFIDUDIN
Abstract : Intensive reaserch that has been doing in various major of research supporting for implementation of the third generation of mobile telecommunication is required. One important think is the error control scheme to be impleted. This thesis evaluated the perfomance of a kind of error control scheme in W-ATM network based on CDMA which implemented in physical layer with Forward Error Control (FEC). The FEC which implemented is concatenated code with Reed Solomon code as inner code and Convolusional Code as outer code. Bit error rate performance that can be reach has been taken to be evaluated in this thesis. For that purpose the simulation has been done with the transmission modeled from the transmiter to the reciver in CDMA condition with generation of CBR and VBR packet as an information reasource. In according to the experiment result, the concatenated code with convolutional code with r =13 has the ability to be implemented in W-ATM network. Free error conditon can be reach at Eb/No = 10 dB with the number of packet = 100 packe, EbNo = 9 dB with the number of packet = 200 packet.